PELATIHAN PEREGANGAN STATIS LEBIH MENINGKATKAN KELENTUKAN DARI PADA PELATIHAN PEREGANGAN DINAMIS PADA SMA NEGERI KUPANG TIMUR - Giyanto, Tri; Sutjana, I Dewa Putu; Maria Boleng, Lukas (Sport and Fitness Journal; Volume 1, No.2, 2013, 2013)
Human exercise aims to improve physical fitness. Physical fitness need to be trained and maintained by training the physical condition of the human element. One element is the physical condition of flexibility. Several factors affect the body's flexibility is muscle, tendon, ligament, and joint structure type, age, sex, body temperature and muscle temperature, body weight and height and genetics. Flexibility can be enhanced by using one of four methods namely method of dynamic stretching, static, passive and Neuromuccular Proprioceptive Facilitation (PNF). This study aims to determine the increase in torso flexibility using dynamic stretching and static stretching methods. The study design was a pretest - posttest control group design to high school students in Kupang district. Large sample of 28 people divided into 2 batches each group totaled 14 people. Each group was asked to perform stretching exercises the same type by using two different methods namely dynamic and static stretching methods. The results were tested by the Normality Test Shapiro Wilk Test showed that the value of p> 0.05 so that the two groups are stretching normal distribution. Homogeneity test with Test of homogeneity of variance showed that the value of p> 0.05, then Ho is accepted. So both the stretching group had the same variant or homogeneous. Increased flexibility test with Paired Sample T Test showed that the value of P <0,05. Means the average of the data flexibility after training in both groups significantly different or significantly. T-indpendent test showed p values??> 0.05, whereas after pepelatihan has a p-value <0.05. This shows the average increase flexibility before and after treatment in both groups was significantly different. The conclusion of this study that further enhance the training of static stretching on torso flexibility of dynamic stretching training in high school student Kupang. It is recommended to increase the flexibility of the coaches, PE teachers and sportsmen using static stretching exercises, or by combining both the stretch.
Keywords: torso flexibility, training, dynamic stretching, static stretching, biomotoric components.